1979
DOI: 10.1139/z79-222
|View full text |Cite
|
Sign up to set email alerts
|

Development and survival of embryos and alevins of the Atlantic salmon, Salmo salar L., continuously exposed to acidic levels of pH, from fertilization

Abstract: Embryos and subsequent alevins of the Atlantic salmon, Salmo salar L., were incubated continuously from fertilization to a time 40 days after hatching at six levels of pH, 6.8 (control), 5.0, 4.5, 4.2, 4.0, and 3.7, at 5–6 °C. Embryos had an LL50 of pH 3.9. The rate of embryonal development was not retarded by these levels. The LL50 for alevins was pH 4.3. Externally deformed alevins were few and not related in frequency to particular levels of pH. Populations of Atlantic salmon will decline and ultimately dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…However, Oyen et al (1991) has found high percentage of deformity between 4.75 and 5.5 water pH. Contrary to this, no relationship between larval deformation and water pH was found in Salmo salar (Daye and Garside 1979;Peterson et al 1989). Hence, it seems that certain fish have high tolerance to water pH.…”
Section: Resultsmentioning
confidence: 94%
“…However, Oyen et al (1991) has found high percentage of deformity between 4.75 and 5.5 water pH. Contrary to this, no relationship between larval deformation and water pH was found in Salmo salar (Daye and Garside 1979;Peterson et al 1989). Hence, it seems that certain fish have high tolerance to water pH.…”
Section: Resultsmentioning
confidence: 94%
“…Since the most acidsensitive ontogenetic stages of brown trout are those from freshly fertilized ova to yolk sac fry (Daye & Garside, 1979), only a small proportion of ova is likely to hatch, enforcing annual bottlenecks during snow melt. The final population displaying reduced polymorphism, Eckbach (El) (He=0.0366; P=0.114), is isolated by a weir preventing immigration, and has never been stocked.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prolonged duration of egg development was observed by Daye and Garside (1979) and Rask (1983). In common carp, Jezierska and Witeska, (1995) revealed that the eggs incubated at the level of pH 4.5 and 10.5 5 did not develop longer than 24h.…”
Section: Discussionmentioning
confidence: 96%